Gap between patients with schizophrenia and their psychiatrists on the needs to psychopharmacological treatment: A cross‐sectional study - Kie Takahashi; Ryoko Yamazawa; Takefumi Suzuki; Masaru Mimura; Hiroyuki Uchida (Wiley, 2020)
Abstract Aim Psychopharmacological treatment is indispensable in patients with schizophrenia but data on needs, preferences, and complaints about their medications are limited. Moreover, there has been no study to assess the degree of awareness of their psychiatrists (gap in needs) regarding these issues. Methods Ninety‐seven Japanese patients with schizophrenia (ICD‐10) were asked to fill in the questionnaire consisting of multiple‐choice questions regarding (a) their needs and complaints about psychopharmacological treatment that they were receiving, and (b) their preference of dosage form, dosing frequency, and timing of dosing. Additionally, their psychiatrists in charge were asked to predict their patients' response to the above questions. Results Both the most frequently endorsed need and complaints about the current psychopharmacological treatment were "nothing in particular" (n = 14, 16.7% and n = 17, 20.2%); merely 23.1% and 15.4% of their psychiatrists correctly predicted these responses, respectively. "Once a day" (n = 56, 65.1%), "at bedtime" (n = 53, 61.6%), and "tablet" (n = 51, 59.3%) were the patients' most favorite dosing frequency, timing, and dosage form, respectively; 59.8% (n = 49), 54.9% (n = 45), and 64.6% (n = 53) of their psychiatrists predicted them. Conclusions These findings suggest that there is substantial room for improvement on the side of psychiatrists to capture their patients' needs and complaints about psychopharmacological treatment.